Deformation of the Cross Section of the Surface of Erythrocyte in the Plane of Mirror Symmetry in the Field of Ionizing Radiation - V. E. Mkrtchian; H. G. Badalyan
In the frame of Helfrich spontaneous curvature model, a general equation of the curvature of the crosssection of the surface of erythrocyte in the plane of mirror symmetry in the field of isotropic radiationis derived in detail. It is shown that despite of the case of erythrocyte surface equation which contains three independent phenomenological parameters (osmotic pressure, tensile stress and spontaneous curvature), the shape of the contour of the cross section is defined via two of them: osmotic pressure and the linear combination of square of spontaneous curvature and tensile stress. In the case of small intensities of radiation is found that the intensity of radiation and the isoperimetric parameter of the contour are connected via a transcendental equation.
Keywords: Physics; Cross-Disciplinary